QUALITY OF LIFE THROUGH LISTENING MUSIC AMONG ELDERLY PEOPLE IN SEMI-URBAN AREA, THAILAND - Wattanasoei, Supang; Binson, Bussakorn; Kumar, Ramesh; Somrongthong, Ratana; Kanchanakhan, Naowarat (Journal of Ayub Medical College Abbottabad, 2017)
Background: Aging is one of the biggest problems in Southeast Asia due to their rapidly growing population of the older person. Old aging population is usually confined to their homes resulting in poor quality of life (QOL). Music has been found to be the great activity for older peoples with physical, emotional and social disorders hence, it affects on quality of their life. This study explored the music preference among elderly people and their quality of life in the semi-urban of Thailand. Method: A cross-sectional study was conducted by interviewing 353 elderly individuals living in the semi-urban area of Thailand. A validated, reliable world health organization quality of life (WHOQOL-OLD) tool was adapted for this study. Logistic regression analysis was performed to identify the factors associated with QOL and its six domains with adjusted covariates, and the potential factors including chronic disease, community participation, traditional event participation, the experiences of music listening, and the types of music preference were entered in the model. Results: Findings revealed that more than half of respondents were married female with an average age of 68.92±6.99. Around (80.7%) suffered from chronic diseases and the hypertension was found the highest (66.32%). The quality of life among the elderly was found at the moderate level with the total QOL score of 83.41±SD=10.32. Respondents with chronic diseases have the total QOL score (OR=0.95, 95% CI 0.93-0.98). Respondents who preferred to listen to Look Krung (Thai popular classic music) type have the total QOL score (OR=1.03, 95% CI 1.01-1.05), Autonomy Facet(AUT) score (OR=1.11, 95% CI 1.02-1.21), and Intimacy facet(INT) score (OR=1.14, 95% CI 1.05-1.24) as compared to those who did not listen the music. Conclusion: The study highlights the relationship between the QOL among aging people and the listening of music in the semi-urban area of Thailand. Keywords: Quality of Life; Music Preference; Elderly and Aging life